2014
DOI: 10.1111/ane.12305
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to caregivers' stress and burden in Parkinson's disease

Abstract: Disability (ADLS) and mood (BDI) of patients with PD are the main factors contributing to burden and stress in caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 48 publications
9
82
1
1
Order By: Relevance
“…Mobility impairment, as well as activities of daily living, have been reported as a burden for caregivers [21]. Increasing disabilities in PD construct a stigma that can lead to social isolation and emotional distress, which, in turn, causes burden to caregivers [22].…”
Section: Discussionmentioning
confidence: 99%
“…Mobility impairment, as well as activities of daily living, have been reported as a burden for caregivers [21]. Increasing disabilities in PD construct a stigma that can lead to social isolation and emotional distress, which, in turn, causes burden to caregivers [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sixty‐eight PD patients from the cohort ( n = 150) (Santos‐García and de la Fuente‐Fernández , ) were receiving DA therapy at baseline: 30 pramipexole, 20 rotigotine, 17 ropinirole, and one pramipexole + rotigotine. Seven patients died and two cases (taking ropinirole) were lost to follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a retrospective chart review of the follow‐up of a subgroup of nondemented PD patients receiving a DA ( n = 68; 60.3% males, 69.3 ± 9.2 years old) from a cohort ( n = 150) previously studied in detail (Santos‐García and de la Fuente‐Fernández , ). The patients from the cohort who were receiving a DA, such as pramipexole, ropinirole, and rotigotine at baseline (cross‐sectional study conducted in 2012) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a chronic and progressive neurodegenerative disorder characterised by physical and psychological symptoms that result in motor disability, neuropsychiatric symptoms and loss of autonomy [1, 2]. PD is the second most common neurodegenerative disorder after Alzheimer’s disease affecting approximately 1-2 % of the population over 60 years of age and 4 % of those aged 80 years worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
“…These common manifestations that affect the quality of life (QoL) of carers of individuals with PD are frequently associated with the severity of symptoms of patients, progression disease and patient disability [14]. Several studies examining the role of caregiving in Spain and other Western European countries have found that patient disability and mood disturbances contribute to caregiver’s burden and stress as well as placing strain on the family unit as a whole [1, 16, 17]. In addition, the demands of caring may result in an increase in marital dissatisfaction since caregiving may result in a lack of leisure activities, social isolation and low levels of perceived social support [18].…”
Section: Introductionmentioning
confidence: 99%